2013
DOI: 10.1159/000351107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Treatment with Ambroxol and Ciprofloxacin on Catheter-Associated <b><i>Pseudomonas aeruginosa</i></b> Biofilms in a Rat Model

Abstract: Background:Pseudomonas aeruginosa is an opportunistic pathogen that causes potentially devastating infections in immunocompromised patients. These infections are particularly difficult to treat if a biofilm forms, which is likely if foreign bodies are present. Objective: This study aimed to investigate the effect of ambroxol combined with ciprofloxacin on P. aeruginosa biofilm in a rat model. Methods: A rat model of acute lung infection was created by endotracheal (ET) intubation with a tube covered with a P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
12
0
2
Order By: Relevance
“…Second, ambroxol can promote the permeability of vancomycin through S. epidermidis biofilms. It has been reported that ambroxol promotes the permeability of ciprofloxacin through P. aeruginosa biofilms [15]. Conventionally, the antimicrobials are only able to diffuse through the biofilm shallowly and kill bacteria located shallow in the biofilms [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, ambroxol can promote the permeability of vancomycin through S. epidermidis biofilms. It has been reported that ambroxol promotes the permeability of ciprofloxacin through P. aeruginosa biofilms [15]. Conventionally, the antimicrobials are only able to diffuse through the biofilm shallowly and kill bacteria located shallow in the biofilms [31].…”
Section: Discussionmentioning
confidence: 99%
“…Divided catheter segments were fixed in 2% glutaraldehyde solution as described in previous studies [15]. Following dehydration, catheters were coated with platinum-palladium and viewed under a JSM-35C scanning electron microscope (JEOL, Tokyo, Japan).…”
Section: Microbiology Of the Cathetersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol was added to dissolve the crystal violet, and the absorbance was measured at 570 nm. Meanwhile, bacterial adhesion was also observed by light microscopy (Nikon, Japan) and a plate counting method [10]. For the plate counting method, briefly, 24-well plates were washed 3 times using sterile PBS, and 1 ml PBS was added.…”
Section: Bacterial Adhesion Biofilm Biomass and Confocal Laser Scanmentioning
confidence: 99%
“…Briefly, 96-well plates were washed 3 times using sterile PBS, and 100 ml of BHI medium was added. Then, the plate was sealed with parafilm and agitated for 30 min with an ultrasonotor (1 MHz) [10], and 10 ml CCK-8 was added. After 4 h of incubation, the absorbance at 450 nm was measured.…”
Section: Live Bacteria and Live P Aeruginosa/s Mitis In The Biofilmmentioning
confidence: 99%